Investigation Of Drug Nutrient Interactions And Physicochemical Compatibilities Of Ceftazidime, Cefotaxime And Cefepime In Neonatal Total Nutrient Admixtures Using Hplc - Iqbal, Muhammad Shahid (2013)
and trace elements). The stability of the formulations were evaluated for various physicochemical parameters such as pH, globule size, zeta potential, precipitation, flocculation, coalescence and concentrations of sodium, potassium and drug concentrations. The experiments were carried out at room temperature (25±2°C) and samples were collected at 0, 4, 8, 16 and 24 hours respectively. Antibiotic concentrations in the samples were analyzed by using the newly developed and validated HPLC methods. SPE was used by modification of the mobile phase and washing solvents in different ratios to achieve better accuracy, precision, linearity, earlier retention times, clear elution and recovery. The study showed that ceftazidime and cefepime were stable for up to 16 hours while cefotaxime was stable for up to 24 hours in all TNAs formulations and there after degraded more than 10% respectively. Physico-chemical compatibility results showed that there were no significant changes in pH, globules size, zeta potential and concentrations of sodium and potassium in all of the formulations (all p >0.05). In addition, there was no precipitation or flocculation observed in any of the formulation. The newly developed HPLC methods were able to detect selected cephalosporins more accurately, precisely, effectively and efficiently. In conclusion, this study showed that ceftazidime and cefepime were compatible and stable for 16 hours in/with TNAs while cefotaxime was compatible and stable for 24 hours in/with TNAs.